Efficiency improvement of dual three-phase permanent magnet synchronous motor using modified switching table DTC for electric ship propulsion - Aziz El Afia; Mhammed Hasoun; Mohamed Khafallah; Karim Benkirane (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
A direct torque control using a classical switching- table ST-DTC can be used to control the torque and thus the speed of Dual Three-Phase Permanent Magnet Synchronous Motor (DTP-PMSM). The principle is based on direct application of control sequence by using two hysteresis regulators and a switching table. A large stator current containing low order harmonics is produced during the application of the classic ST-DTC technique, this leads to higher losses affecting the efficiency of the machine. To allow a reduction of these harmonics a modified switching-table approach based DTC technique is examined. Indeed, an improved ST-DTC strategy, which consist of replacing the vectors of the classical table with synthetic vectors, is discussed. The simulation results confirm the validity of the selected strategy.